The Role of School Libraries in Building a Culture of Literacy from an Early Age (Study at Nurul Chotib Al-Qodiri IV Preschool and Kindergarten, Jombang District, Jember Regency) - Diyaul Widdi Anjani; Elviana Tika Putri; Faiqoh Faiqoh; Rusdiana Navlia (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Early literacy is a crucial foundation for children's academic success and holistic development. School libraries play a strategic role in fostering a culture of literacy, but their utilization in early childhood education institutions is often suboptimal. This article aims to analyze the role of school libraries in building a culture of literacy from an early age, by referring to the practices and challenges faced at PAUD-TK Nurul Chotib Al-Qodiri IV, Jombang, Jember. The discussion is conducted by synthesizing findings from three main studies: library utilization for bibliotherapy, the influence of interactive flashcards on early reading skills, and an analysis of departmental library management. The method used is a literature review with a qualitative-descriptive approach. The results of the discussion indicate that the role of libraries is not limited to passive reading spaces, but can be expanded to become bibliotherapy centers for social-emotional development, early literacy laboratories based on interactive media (such as digital flashcards), and professionally managed learning resource centers. The main obstacles include limited collections, human resources for management, infrastructure, and promotion. In conclusion, optimizing the role of the library at PAUD-TK Nurul Chotib Al-Qodiri IV requires a management transformation from merely storing books to an active, integrated, and enjoyable literacy ecosystem.